Knowledge and Attitudes as Determinants of Behavior in Maintaining Personal Hygiene During Menstruation - Lucia Yogyana Suramas; Bahtiar Bahtiar; Yosefa Anggraeni Mateus Paberu; Betriani Disik; Yosafat Fictoria Senen (Aloha International Journal of Health Advancement (AIJHA), 2025)
Adolescents who have menstruated need to know about the body and reproductive organs, physical and psychological changes, so that they can protect themselves from risks that threaten the health and safety of the function of the reproductive organs. Neglect of reproductive health can cause infections of the reproductive organs and affect infertility or sterility. One of the risk factors for reproductive tract infections is poor menstrual hygiene. This research aimed to analyze the relationship between knowledge and attitudes and the behavior of maintaining personal hygiene during menstruation among Class XI students at SMKS Lakipadada. This research was a cross-sectional study. The respondents were 53 female students at the Lakipadada Vocational School from class XI, consisting of nursing majors = 21 people, TKJ majors = 17 people, pharmacy majors = 15 people, selected using total population sampling. All variables were measured through filling out a questionnaire. The collected data was analyzed using Chi-square test. The p-value for the correlation analysis between knowledge and behavior was 0.000, so it was interpreted that knowledge was correlated with behavior in maintaining personal hygiene during menstruation. The same result (p = 0.000) was obtained from the results of the correlation analysis between attitude and behavior, so it was interpreted that attitude was correlated with the behavior of maintaining personal hygiene during menstruation. Based on the research results, it could be concluded that there is a relationship between knowledge and attitudes and the behavior of maintaining personal hygiene during menstruation in class XI female students at SMKS Lakipadada, Tana Toraja. Keywords: menstruation; female student; personal hygiene; knowledge; attitude; behavior